A new species of Senecio (Compositae, Senecioneae) from Ecuador - Calvo, Joel; Freire, Efraín; Sklenář, Petr (Phytotaxa, 2016)
Senecio alatopetiolatus is described as a new species from the Ecuadorian Andes on the basis of morphological characters. It is a subshrub characterized by having a scandent habit, discoid nodding capitula, middle cauline leaves with winged petioles, and an indumentum composed of glandular-hirsute and sericeous trichomes.